2022
DOI: 10.1186/s43141-022-00376-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of preferentially expressed antigen of melanoma (PRAME) gene expression with clinical characteristics in acute leukemia patients

Abstract: Background Preferentially expressed antigen of melanoma (PRAME) gene is regularly overexpressed in acute leukemia (AL) and other malignant diseases which are recognized by human leucocyte antigen (HLA-24) located in the human chromosome of 22q11 coded by 509 amino acids. To rule out the PRAME gene expression in AL patients and its correlation with clinical characteristics in the Indian population set up by RT-qPCR. Results A total of 42 samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In another recent study, a total of 42 samples from an Indian cohort that comprised of 22 AML, 14 ALL, and 6 other forms of leukemia showed that PRAME was highly expressed in 27 (64.28%) AL patients compared to the lowest expression in healthy individuals. There was no correlation between the PRAME gene expression and clinical parameters [86].…”
Section: Prame As a Biomarkermentioning
confidence: 82%
“…In another recent study, a total of 42 samples from an Indian cohort that comprised of 22 AML, 14 ALL, and 6 other forms of leukemia showed that PRAME was highly expressed in 27 (64.28%) AL patients compared to the lowest expression in healthy individuals. There was no correlation between the PRAME gene expression and clinical parameters [86].…”
Section: Prame As a Biomarkermentioning
confidence: 82%